Institutional isomorphism and community politicisation: A theoretical and empirical comparison between Indonesia and Japan - Seala Syah Alam; Sudarsono Hardjosoekarto; Arthur Josias Simon Runturambi; Chairul Muriman Setyabudi (Jurnal Civics: Media Kajian Kewarganegaraan, 2026)
This research aims to explore how global pressures, international standards, and institutional structures affect the development and effectiveness of community politicisation, focusing on the similarities and differences between the two countries. This research uses a qualitative method, analysing secondary data from interviews, digital platforms, and public sources, complemented by textual analysis and social network analysis. These findings highlight the key role of isomorphism in standardising politicisation practices, with Indonesia and Japan both adopting community politicisation models to increase public trust and cooperation. However, significant differences were observed in the execution of these models, especially in the level of community involvement and the historical context of their implementation. While Japan's political system has matured through policies and structures such as "koban" and "chuzaisyo", Indonesia faces challenges related to limited resources and community diversity. The research concludes that the success of community politicisation depends on the effective adaptation of isomorphisms to local needs, emphasising the importance of community participation, human resource development, and periodic evaluations for sustainability and effectiveness. Further research should explore the impact of local adaptation and innovation on community politicisation outcomes.